P-98 The dilemma of advance directives in the ICU – proxies' and physicians' divergent assessment of their applicability. (1st September 2015) - Leder, N; Schwarzkopf, D; Skorsetz, U; Reinhart, K; Hartog, CS
Abstract : Background: Retrospective studies suggest that advance directives (ADs) have little impact in the intensive care unit (ICU). Their applicability may be difficult to determine because written validity clauses (VC) inadequately reflect the complexity and uncertainty which characterise advanced critical illness. Aim: We compared proxies' and physicians' assessment of an AD's applicability. Methods: Prospective mixed-method observational study in 4 interdisciplinary ICUs. Fifty mentally incompetent patients had ADs. Semi-structured interviews took place with 88 attending and resident physicians and 19 relatives within 48 h; relatives were followed up after 30 days. Results: ICU mortality was 32%. Most relatives were spouses (68%); 18/19 were legal proxies. All claimed full knowledge of patients' preferences. Compared to physicians, proxies found that ADs were more helpful (p = 0.018) and interpreted ADs more literally (p = 0.018). Nineteen ADs allowed direct comparison of physician and proxy assessment. Eight ADs were judged valid, but only 4 ADs were judged valid by both parties. Relatives were more often uncertain about the applicability of VC. Only 2 ADs were judged to be made specifically for the ICU. After 30 days, 13 (68%) relatives stated that patients' preferences had been fully followed. Discussion and conclusion: Proxies and physicians assess ADs differently, but eventually most relatives perceive that therapy complied with patients' wishes. The dilemma of ADs is due to the fact that proxies expect direct guidance from an AD which is not intended for the ICU and must be interpreted by treating physicians. In future, ADs should include directives for the event of critical illness.